2017
DOI: 10.14238/pi57.6.2017.1571
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors of soil-transmitted helminth infection among elementary school students

Abstract: Background Helminth infection remains a health problem, especially in school-aged children. Mass eradication programs with a single dose of anti-helminthic drugs were employed by the local government in some endemic areas in Bali. However, the effectiveness of the programs has not been well evaluated.Objective To investigate prevalence and possible risk factors of helminth infection, including nutritional status, in elementary school students from endemic areas who participated in mass eradication programs.Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 16 publications
2
10
0
2
Order By: Relevance
“…Not washing hands after playing the soil can increase risk of being infected with STH by twelve times in elementary students. These results are in line with the research results obtained by Wiryadana et al 14 In addition, which researcher also was found that children who are barefoot when they are outside the house was also significantly associated with the incidence of STH infection. Being barefoot can cause the occurrence of Ascaris lumbricoides infection.…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…Not washing hands after playing the soil can increase risk of being infected with STH by twelve times in elementary students. These results are in line with the research results obtained by Wiryadana et al 14 In addition, which researcher also was found that children who are barefoot when they are outside the house was also significantly associated with the incidence of STH infection. Being barefoot can cause the occurrence of Ascaris lumbricoides infection.…”
Section: Resultssupporting
confidence: 91%
“…In line with Kartini's 21 research which was stated that is a relationship between children who were barefoot against STH infection, but in Wiryadana et al 14 study, no significant results were found. 14,21 Researcher was also found that children who did not have latrines had a significant association with the incidence of STH infection. However researcher was found the protective value of children who have latrines.…”
Section: Resultsmentioning
confidence: 59%
See 2 more Smart Citations
“…Tidak ditemukan hubungan antara status kecacingan dengan status gizi yang buruk, walaupun sebagian siswa memilki status gizi yang dibawah nilai rekomendasi WHO. Hasil penelitian lebih lengkap telah dipublikasikan secara terpisah yang dapat dilihat pada tautan https://www.paediatricaindonesiana.org/index.php/paediatrica-indonesiana/article/view/1571 (Wiryadana et al 2017).…”
Section: Hasil Dan Pembahasanunclassified